2003
DOI: 10.4049/jimmunol.170.12.6257
|View full text |Cite
|
Sign up to set email alerts
|

A Prominent Role for Airway Epithelial NF-κB Activation in Lipopolysaccharide-Induced Airway Inflammation

Abstract: To reveal the causal role of airway epithelial NF-κB activation in evoking airway inflammation, a transgenic mouse was created expressing a mutant version of the inhibitory protein I-κBα. This I-κBα superrepressor (I-κBαSR) acts to repress NF-κB activation exclusively in airway epithelial cells, under the transcriptional control of the rat CC10 promoter (CC10-I-κBαSR). Compared with transgene-negative littermates, intranasal instillation of LPS did not induce nuclear translocation of NF-κB in airway epithelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
153
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(171 citation statements)
references
References 68 publications
17
153
0
1
Order By: Relevance
“…Previous studies manipulating the NF-B pathway using tissue-specific transgenes (20,22), bone marrow chimeras (17,48,49), and adenoviral vectors (19,21) suggest that NF-B activity in epithelial cells is involved in and/or necessary for initiating inflammatory responses elicited by Gram-negative stimuli. We conducted experiments using alveolar/bronchial epithelial-specific SPC-dnI B␣ transgenic mice to complement our findings in mice lacking RelA in all cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies manipulating the NF-B pathway using tissue-specific transgenes (20,22), bone marrow chimeras (17,48,49), and adenoviral vectors (19,21) suggest that NF-B activity in epithelial cells is involved in and/or necessary for initiating inflammatory responses elicited by Gram-negative stimuli. We conducted experiments using alveolar/bronchial epithelial-specific SPC-dnI B␣ transgenic mice to complement our findings in mice lacking RelA in all cells.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways all converge on the Rel/Nf-kB complex, which is translocated to the nucleus to regulate gene transcription. Recent studies have shown that bronchial epithelial cells express nuclear RelA in response to allergen or lipopolysaccharide-induced inflammation (Poynter et al, 2002(Poynter et al, , 2003(Poynter et al, , 2004. This is evidence that Nf-kB can act directly within airway epithelial cells but the downstream targets are not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…This feedback mechanism might be a critical factor in explaining why lung epithelial cells eventually die in hyperoxia even though NF-κB activation was initiated by hyperoxia [16,45]. Together with its role in sensitizing the airway epithelium to oxidative apoptosis, the regulation of the steadystate levels of IκBα might be an important modulator of oxidative lung injury and pulmonary remodeling [70,77,[82][83][84][85].…”
Section: Redox Transcription Factors In Pulmonary Hyperoxic Cell Deathmentioning
confidence: 99%